2017
DOI: 10.1186/s12893-017-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel variation of the recurrent laryngeal nerve

Abstract: BackgroundInjury to the recurrent laryngeal nerve is one of the most severe complications of thyroid surgery. Several anatomic variations of the nerve increase the likelihood of iatrogenic damage.Case presentationA 50-year-old woman was presented to our department with a nodule in the right thyroid lobe, and she reported no voice changes. She had no history of surgery or radiation to the head or neck. Fine-needle aspiration was recorded as papillary thyroid carcinoma. The preoperative laryngoscopy revealed lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Regarding the sex of the population studied in the articles with a total sample size equal to 1, the following characteristics were identified: 5 subjects were men (27.7%), 12 subjects were women (66.66%), and 1 study did not report the sex of the sample (5.55%). In relation to the 23 studies that presented a sample size greater than 1, the following data were collected: 5 studies [ 8 , 11 , 13 , 28 , 29 ] did not specify the sex of the subjects with a total sample size of 6531 (22.36% of the total sample of studies with a sample greater than 1; 2 studies [ 31 , 32 ] presented only women in their sample, which is equivalent to 10 (0.034% of the total sample of studies with a sample size greater than 1); finally, 16 studies [ 3 , 11 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] included both men and women in their sample and the following data were obtained: the total number of men was 4849 (16.6%) and that of women was 17,810 (60.99%). Individually, in the studies that presented both men and women, the percentage of men varied between 4.08% and 81% and had a mean of 26.64, while the percentage of women varied between 19% and 95.92% with a mean of 73.36% (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the sex of the population studied in the articles with a total sample size equal to 1, the following characteristics were identified: 5 subjects were men (27.7%), 12 subjects were women (66.66%), and 1 study did not report the sex of the sample (5.55%). In relation to the 23 studies that presented a sample size greater than 1, the following data were collected: 5 studies [ 8 , 11 , 13 , 28 , 29 ] did not specify the sex of the subjects with a total sample size of 6531 (22.36% of the total sample of studies with a sample greater than 1; 2 studies [ 31 , 32 ] presented only women in their sample, which is equivalent to 10 (0.034% of the total sample of studies with a sample size greater than 1); finally, 16 studies [ 3 , 11 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] included both men and women in their sample and the following data were obtained: the total number of men was 4849 (16.6%) and that of women was 17,810 (60.99%). Individually, in the studies that presented both men and women, the percentage of men varied between 4.08% and 81% and had a mean of 26.64, while the percentage of women varied between 19% and 95.92% with a mean of 73.36% (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the clinical relationships reported by the studies included in this review, three studies did not report any type of clinical consideration related to the RLN and NRLN variants [ 45 , 49 ]. Thirty-eight studies reported clinical considerations associated with RLN and NRLN variants, which are as follows: 16 studies, within their results, reported possible injuries arising from surgical complications associated with surgeries such as thyroidectomies, parathyroidectomies, esophagectomies, laryngeal surgeries, or any other type of surgery of the cervical region surrounding the RLN and NRLN.…”
Section: Clinical Considerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main motor nerve of the throat, the RLN was mainly responsible for the control of swallowing [19]. e degree of RLN injury was one of the indicators of the success of surgical treatment, and it was the most serious complication after TN [20]. e results of this study showed that the PPIR of RLN in the malignant TN group was higher in contrast to group B during the three months after the surgery, and the difference was dramatic (P < 0.01).…”
Section: Discussionmentioning
confidence: 99%